Four-year results of a prospective-controlled clinical study evaluating healing of intrabony defects following treatment with an enamel matrix protein derivative alone or combined with a bioactive glass - Anton Sculean (Blackwell Synergy, 2007)
Aim: To evaluate the 4-year results following regenerative periodontal surgery at intra-bony defects with either a combination of an enamel matrix protein derivative (EMD) and a bioactive glass (BG) or with EMD alone. Methods: Twenty-five patients with one deep intra-bony defect each were randomly treated with either an EMD1BG (test) or with EMD alone (control). Measurements were recorded at baseline, at 1 and at 4 years following therapy. The primary outcome variable was the clinical attachment level (CAL). Results: The test group demonstrated a mean CAL change from 10.3 1.6 to 6.7 1.2mm (po0.001) and to 6.9 1.0mm (po0.001) at 1 and 4 years, respectively. No statistically significant differences were found between the 1- and 4-year results. The control group showed a mean CAL change from 10.4 1.6 to 6.7 1.1mm (po0.001) at 1 year and 7.0 0.9mm (po0.001) at 4 years. The CAL change between 1 and 4 years did not present statistically significant differences. In each of the two groups, four defects have lost 1mm of the CAL gained at 1 year. A CAL gain of 1mm compared with the 1-year results was measured in only one defect of the test group. Compared with baseline, a CAL gain of X3mm was found at 4 years in 10 defects in both groups. Between the treatment groups, no statistically significant differences in any of the investigated parameters were observed at 1 and at 4 years. Conclusions: Within their limits, the present results indicate that the clinical improvements obtained with both regenerative modalities can be maintained over a period of 4 years.